Polysemy and visual rhetoric: Bridging ambiguity and multicultural expression meanings in product packaging. - Ahmad Fauzi, Farrah Hanani; Che Cob, Saiful Akram; Adzmi , Mohd. Hafnizam; Mohd Radzuan , Lili Eliana (Journal of Islamic, Social, Economics and Development, 2025)
Polysemy and visual rhetoric: Bridging ambiguity and multicultural expression meanings in product packaging.